Musical symbols - Koter, Darja (Muzikološki zbornik, 2014)
The interpretation of musical symbols the frescos, paintings and architectural details could explain the spiritual dimension of the symbolism. Some examples from the Slovenian art heritage of churches and palaces from the 16th to 18th century demonstrate the interplay between religious and secular content, which suggests that the symbolic value of the depictions is a priority, while the selection of themes which could be more or less spiritual or/and secular are not of the greatest significance.
Keywords: glasbena ikonografija; glasbeni instrumenti; likovna dediščina; simbolika